2014
DOI: 10.1093/trstmh/tru148
|View full text |Cite
|
Sign up to set email alerts
|

High dose corticosteroids in severe leptospirosis: a systematic review

Abstract: The role of corticosteroids in the treatment of severe leptospirosis is unclear. The rationale for their use is that, in severe leptospirosis, there is a severe immunological response that is harmful to the host resulting in multi-organ dysfunction, which is potentially offset by the nonspecific immunosuppression of high dose steroids. We conducted a systematic review of studies that have assessed the use of high dose corticosteroids in patients with severe leptospirosis by searching MEDLINE and Scopus SciVers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…57, 58, 59 In this study, we observed an alleviation of pulmonary hemorrhage in TLR4 −/− mice, possibly due to suppression of the ‘storm’ of proinflammatory cytokine production. This suggests the potential of combining TLR4 blockade and antibiotics in the treatment of severe leptospirosis with manifestations of pulmonary hemorrhage.…”
Section: Discussionsupporting
confidence: 54%
“…57, 58, 59 In this study, we observed an alleviation of pulmonary hemorrhage in TLR4 −/− mice, possibly due to suppression of the ‘storm’ of proinflammatory cytokine production. This suggests the potential of combining TLR4 blockade and antibiotics in the treatment of severe leptospirosis with manifestations of pulmonary hemorrhage.…”
Section: Discussionsupporting
confidence: 54%
“…7 Renal support in the form of dialysis is often required, although there are few studies addressing the role of dialysis in leptospirosis. There is currently no firm evidence regarding the place of immunological therapy, such as corticosteroids 8 or immunoglobulins.…”
Section: Management Of Leptospirosismentioning
confidence: 99%
“…This has led to recent reports of novel approaches to treatment including the use of inhaled nitric oxide and desmopressin (17,18). Although the benefits of corticosteroids in the treatment of ARDS are known, evidence for use of corticosteroids in pulmonary leptospirosis is confined to occasional case reports or small studies (19). Neither of these options were used in our case.…”
Section: Discussionmentioning
confidence: 93%